Population, employment, and wages: A comparative study on North Arcot villages, 1973-1983 - Harriss, John (International Food Policy Research Institute, 1991)
One aspect of the research undertaken in North Arcot in 1973/74 by the Cambridge project was a comparative study of the sample villages.